Viroporins in the influenza virus - To, Janet (2020)
Influenza is a highly contagious virus that causes seasonal epidemics and unpredictable pandemics. Four influenza virus types have been identified to date: A, B, C and D, with only A–C known to infect humans. Influenza A and B viruses are responsible for seasonal influenza epidemics in humans and are responsible for up to a billion flu infections annually. The M2 protein is present in all influenza types and belongs to the class of viroporins, i.e., small proteins that form ion channels that increase membrane permeability in virus-infected cells. In influenza A and B, AM2 and BM2 are predominantly proton channels, although they also show some permeability to monovalent cations. By contrast, M2 proteins in influenza C and D, CM2 and DM2, appear to be especially selective for chloride ions, with possibly some permeability to protons. These differences point to different biological roles for M2 in types A and B versus C and D, which is also reflected in their sequences. AM2 is by far the best characterized viroporin, where mechanistic details and rationale of its acid activation, proton selectivity, unidirectionality, and relative low conductance are beginning to be understood. The present review summarizes the biochemical and structural aspects of influenza viroporins and discusses the most relevant aspects of function, inhibition, and interaction with the host.